Diagnostic and therapeutic conduct in wounds of the aerodigestive tract - Torterolo, Edgardo; Gateño, Nisso (Cirugía del Uruguay, 1974)
Visceral lesions are rare in patients that reach the hospital alive. When they do exist, concomitant aerial and digestive lesions are frequently found. Their diagnosis is discussed with stress on the importance of respiratory obstruction, both immediately and in the post-operatory period. F'inally, therapeutical managernent of these wounds is revised.